Mechanical behavior of BCC-superalloys - Wang, Qing; Wang, Zhenhua; Wang, Rui; Knowles, Alexander J.; Zenk, Christopher; Song, Gian; Lee, Chanho; Liaw, Peter K.; Wang, Tongmin (Scripta Materialia, 2025)
Body-centered-cubic (BCC)-base superalloys primarily containing refractory elements have great potential as one kind of ‘beyond Ni-base superalloy’ materials, owing to their increased melting points and analogous coherent microstructures composed of BCC solid solution and its ordered B2 or L21 phases. The mechanical behavior of BCC superalloys (including ferritic and refractory superalloys) is a key topic that has been progressively investigated. However, major challenges remain in terms of room-temperature brittleness and high-temperature creep resistance, as well as mechanical property degradation induced by the coarsening of BCC-B2/L21 coherent microstructure or/and brittle phase precipitation. This viewpoint paper concentrates on the capability and issues regarding the mechanical behavior (strength, ductility, and creep) of BCC superalloys across diverse systems, in which the crucial influence factors are highlighted. Then the ductility challenges of these high-strength superalloys will be discussed. And possible approaches to improve mechanical properties will also be explored for developing novel BCC superalloys.
CRIS-Team Scopus Importer:2025-05-30
Keywords: BCC superalloys; Coherent microstructure; High-entropy alloying; Mechanical properties